Salivary protein polymorphisms and risk of dental caries: a systematic review - Andrea LIPS; Leonardo Santos ANTUNES; Lívia Azeredo ANTUNES; Andrea Vaz Braga PINTOR; Diana Amado Baptista dos SANTOS; Rober BACHINSKI; Erika Calvano KÜCHLER; Gutemberg Gomes ALVES (Sociedade Brasileira de Pesquisa Odontológica, 2017)
Abstract Dental caries is an oral pathology associated with both lifestyle and genetic factors. The caries process can be influenced by salivary composition, which includes ions and proteins. Studies have described associations between salivary protein polymorphisms and dental caries experience, while others have shown no association with salivary proteins genetic variability. The aim of this study is to assess the influence of salivary protein polymorphisms on the risk of dental caries by means of a systematic review of the current literature. An electronic search was performed in PubMed, Scopus, and Virtual Health Library. The following search terms were used: "dental caries susceptibility," "dental caries," "polymorphism, genetics," "saliva," "proteins," and "peptides." Related MeSH headings and free terms were included. The inclusion criteria comprised clinical investigations of subjects with and without caries. After application of these eligibility criteria, the selected articles were qualified by assessing their methodological quality. Initially, 338 articles were identified from the electronic databases after exclusion of duplicates. Exclusion criteria eliminated 322 articles, and 16 remained for evaluation. Eleven articles found a consistent association between salivary protein polymorphisms and risk of dental caries, for proteins related to antimicrobial activity (beta defensin 1 and lysozyme-like protein), pH control (carbonic anhydrase VI), and bacterial colonization/adhesion (lactotransferrin, mucin, and proline-rich protein Db). This systematic review demonstrated an association between genetic polymorphisms and risk of dental caries for most of the salivary proteins.